GP151 Using a modified-TOSBA approach to provide timely, formative feedback to medical students – 18 months experience in tertiary paediatrics. (June 2019) - O'Leary, Daire; Nertney, Leona; Nicholson, Alf
Abstract : Background: Medical student numbers have increased, and medical degree course duration has decreased over recent years. This leads to reduced bedside teaching opportunities which has been implicated in a reduction in clinical skills. In addition, students' desire to receive formative feedback is well documented. Team objective structured bedside assessments (TOSBA) involves structured feedback on observed clinical tasks performed on patients in the small-group clinical tutorial setting. The paediatric rotation in our institution includes six weeks of neonatal and paediatric hospital attachments. Students spend a third of their rotation in tertiary paediatric hospital. Each student is scheduled for two bedside tutorials with each clinical lecturer. In order to provide consistent formative feedback for all students, a decision was made to adopt a modified TOSBA approach to these learning experiences. Methods: A structure for the 60-minute mTOSBA bedside teaching sessions was agreed. Students were briefed on the structure of the session. Within each tutorial group, half the students were observed taking a focused history and the other half performing clinical examination. Tutors facilitated a verbal debrief immediately following the bedside session. In addition, each student received individualized, written, formative feedback. The emphasis was placed on providing formative feedback on communication and clinical skills rather than knowledge; in this way it differed from the original TOSBA described by Miller et al. Results: Over the first 18 months, almost 500 students have attended 1 or 2 mTOSBAs during their tertiary paediatric clinical rotation. Challenges encountered are typical for any bedside teaching session in terms of patient access and interruptions. Specific to mTOSBA, delays in providing written feedback and additional workload for clinical lecturers were noted. After the first year, written feedback was incorporated into the students' portfolio leading to more timely written feedback and reducing duplication of tasks by clinical lecturers. Verbal feedback from students on this mode of teaching has been positive. Conclusions: Formal evaluation of the acceptability and utility of mTOSBA as a tool for providing timely, formative feedback is ongoing. Our experience to date suggests that it is feasible even during a relatively short window with a relatively high student to lecturer ratio.